Anathemas and admirations - Cioran, Emile Michel, 1911-1995; Howard, Richard, 1929-2022; Thacker, Eugene (New York : Arcade Pub., 2012)
Cioran blijft trouw aan zijn stokpaardje: religie.
Keywords: Maistre, Joseph Marie, -- comte de, -- 1753-1821.; Epigrams, French; Literature, Modern -- History and criticism -- 19th century; Literature, Modern -- History and criticism -- 20th century